Sistem Informasi Rental Mobil Berbasis Website Menggunakan Metode Rapid Aplication Development (Studi Kasus: CV. Surya Rent Cars) - Elkin Rilvani; Arif Susilo (Jurnal SIGMA, 2023)
Business in the field of car rental in Indonesia has very promising prospects, because car transportation is the type of transportation most favored by Indonesian people and the trend of car use continues to increase from year to year. Adapaun Surya Rent Car is a company engaged in the field of car rental which in practice its business operational management activities still use the old method or manually. As in managing car data, rental transactions and making rental reports, company admins still use pen and paper, this often results in damage or loss of managed data. The method used in this study as a guide in designing a car rental information system using the Rapid Application Development method. By making this research, it is hoped that it can minimize errors that often occur, speed up work time and provide convenience to company owners in managing company operational data at Surya Rent Cars. Keywords: System, Rental, Website, RAD